Recurrent Sterile Polyserositis Reveals an Underrecognized Autoinflammatory Phenotype in MECP2 Duplication Syndrome - Danielle Mendonca; Matt S. Zinter; Sunjay R. Devarajan; Jason Boehme; Bernhard Suter; Mirjana Maletic‐Savatic; Eyal Muscal; Davut Pehlivan (Clinical Genetics, 2026)
ABSTRACT MECP2 duplication syndrome (MDS) is a rare neurogenetic disorder characterized by neurodevelopmental delay, epilepsy, gastrointestinal dysfunction, and frequent infections. The broader spectrum of immune dysregulation remains poorly understood. We retrospectively reviewed four MDS patients with recurrent sterile polyserositis across multiple centers, analyzing clinical presentation, laboratory findings, treatment responses, and outcomes. All patients developed recurrent pleural and/or pericardial effusions of unclear etiology, with systemic inflammation (leukocytosis, elevated C‐reactive protein, hyperferritinemia in some cases). Extensive workups were unrevealing. Patients also demonstrated evidence of immune dysregulation, including hypogammaglobulinemia, altered T‐ and B‐cell populations, and abnormal immunoglobulin profiles. Effusions persisted despite antimicrobials and drainage, but resolved with immune‐directed therapies. Earlier immunomodulatory therapy enabled faster recovery and reduced morbidity. One patient achieved sustained remission without recurrence with long‐term immunomodulatory treatment. We identify recurrent sterile polyserositis as a previously unrecognized inflammatory manifestation of MDS, suggestive of an autoinflammatory mechanism given the systemic hyperinflammation, absence of infectious or oncogenic causes, and responsiveness to immunomodulatory therapy. Our findings highlight the importance of early immunophenotyping and targeted immunomodulation. Prospective studies are needed to define the prevalence, biology, and optimal management of this emerging inflammatory phenotype.